KENDALA PEMBELAJARAN JARAK JAUH SELAMA MASA PANDEMI COVID-19 DI SDN CIPINANG BESAR SELATAN 19 PAGI JAKARTA - LILIS SUARSIH (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2022)
During the Covid-19 Pandemic, the government established a policy in the process of learning activities, namely by eliminating face-to-face learning in schools temporarily replaced with online distance learning from home with the intention of breaking the chain of transmission of Covid-19. With the outbreak of the Covid-19 pandemic caused many obstacles in the distance learning process at SDN Cipinang Besar Selatan 19 Pagi Jakarta. So the researcher was interested in examining the obstacles to distance learning during the Covid-19 pandemic at SDN Cipinang Besar Selatan 19 Pagi Jakarta. The purpose of this study was to obtain information on the constraints distance learning (PJJ) during the Covid-19 pandemic at SDN Cipinang Besar Selatan 19 Pagi Jakarta. This research uses a qualitative case study method in three ways: observation, interview and documentation. The interview prepared several questions for parents, students and teacher. Observation is done by visiting and to the respondent's house. Documentation in the form of photographs when conducting research. In this study there were 5 respondents, consisting of 2 students at SDN Cipinang Besar Selatan 19 Pagi Jakarta, 2 parents of students, 1 teacher at SDN Cipinang Besar Selatan 19 Pagi Jakarta. The results of the research are constraints on the availability of learning media (handphones, laptops or computers), lack of mastery of science and technology (science technology), constraints on the cost of purchasing internet packages (quotas), time constraints, communication and socialization constraints between students, teachers and parents, constraints on unlimited working hours for teachers. By looking at the results of the research it proves that there were obstacles to distance learning during the Covid-19 pandemic at SDN Cipinang Besar Selatan 19 Pagi Jakarta. ABSTRAKPada masa Pandemi Covid-19 pemerintah menetapkan kebijakan dalam proses kegiatan pembelajaran yaitu dengan meniadakan pembelajaran tatap muka langsung di sekolah sementara waktu diganti dengan pembelajaran jarak jauh dari rumah secara online dengan maksud untuk memutus rantai penyebaran Covid-19.Dengan adanya wabah pandemi Covid-19 banyak menimbulkan kendala dalam proses pembelajaran jarak jauh di SDN Cipinang Besar Selatan 19 Pagi Jakarta.Maka peneliti tertarik untuk meneliti kendala pembelajaran jarak jauh selama masa pandemi Covid-19 di SDN Cipinang Besar Selatan 19 Pagi Jakarta.Tujuan dari penelitian ini adalah untuk mendapatkan informasi kendala pembelajaran jarak jauh (PJJ) selama masa pandemi Covid-19 di SDN Cipinang Besar Selatan 19 Pagi Jakarta.Penelitian ini menggunakan metode studi kasus kualitatif dengan tiga cara yaitu: observasi,wawancara dan dokumentasi.Wawancara dipersiapkan beberapa pertanyaan untuk orang tua siswa,siswa dan guru.Observasi dilakukan dengan cara kunjungan ke rumah responden.Dokumentasi berupa foto-foto pada saat melakukan penelitian .Dalam penelitian ini responden sebanyak 5 orang, terdiri dari 2 orang siswa SDN Cipinang Besar Selatan 19 Pagi Jakarta, 2 orang tua siswa, 1 orang guru SDN Cipinang Besar Selatan 19 Pagi Jakarta.Hasil penelitian yaitu kendala ketersediaan media belajar (Handphone, laptop atau computer), kurangnya penguasaan IPTEK (Ilmu pengetahuan teknologi), kendala biaya pembelian paket (kuota) internet, kendala waktu, kendala komunikasi dan sosialisasi antara siswa, guru dan orang tua, kendala jam kerja yang tidak terbatas bagi guru.Dengan melihat hasil penelitian membuktikan bahwa terdapat kendala pembelajaran jarak jauh selama masa pandemi Covid-19 di SDN Cipinang Besar Selatan 19 Pagi Jakarta.